Youth Work Transitions: A Review with Implications for Counselling and Career Practice - Parada, Filomena; Young, Richard A. (Canadian Journal of Counselling and Psychotherapy, 2012)
We critically review studies highlighting youth’s work transitions and derive some implications for career and counselling theory and practice. We first discuss today’s hypermodern world, specifically the meanings being conveyed by today’s complex social realities and their impact on individuals’ (work) lives. An overview of research, most of it framed from the perspective of current youth studies literature, follows, addressing how today’s youth think, feel, and act while negotiating work transitions. Finally, some implications for career counselling theory and practice are derived, using some of the most recent developments in the career field theory as an integrative framework.